2014
DOI: 10.5539/elt.v8n1p11
|View full text |Cite
|
Sign up to set email alerts
|

EFL Oral Communication Teaching Practices: A Close Look at University Teachers and A2 Students’ Perspectives in Thailand and a Critical Eye from Serbia

Abstract: This paper aimed to reexamine current EFL oral communication teaching practices from the perspectives of teachers and A2 students at two universities, namely Prince of Songkla University (PSU), Thailand and University of Novi Sad (UNS), Serbia. The main objectives were: (1) to analyze current practices from the perspectives of teachers and students, (2) to identify real problems encountered by teachers and students attempting to embrace Communicative Language Teaching (CLT) to improve oral English communicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Though developing EFL learners' oral English communication skills is a complex phenomenon in an EFL context, most of the studies that have been conducted focused on the problems EFL learners face at different levels of education to develop learners' oral skills in different global EFL contexts (Afshar & Asakereh, 2016;Alam, 2013;Alyan, 2013;Khudhair, 2019;Polishchuk, 2018;Tsang, 2017;Yanagi & Baker, 2016). A limited number of studies investigated the problems EFL teachers face at the tertiary level in different global EFL contexts (Abda, 2017;Bruner, Sinwongsuwat, & Radić-Bojanić, 2015;Chen & Goh, 2011;Demir, 2017;García, 2012;Nuraini, 2016) and in Bangladeshi context (Chowdhury & Shaila, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Though developing EFL learners' oral English communication skills is a complex phenomenon in an EFL context, most of the studies that have been conducted focused on the problems EFL learners face at different levels of education to develop learners' oral skills in different global EFL contexts (Afshar & Asakereh, 2016;Alam, 2013;Alyan, 2013;Khudhair, 2019;Polishchuk, 2018;Tsang, 2017;Yanagi & Baker, 2016). A limited number of studies investigated the problems EFL teachers face at the tertiary level in different global EFL contexts (Abda, 2017;Bruner, Sinwongsuwat, & Radić-Bojanić, 2015;Chen & Goh, 2011;Demir, 2017;García, 2012;Nuraini, 2016) and in Bangladeshi context (Chowdhury & Shaila, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides, García (2012), in his qualitative study, reported that lack of learners' oral practice environment, oral activities, and time constraint challenged Mexican EFL teachers to teach and develop learners' oral competency at higher education. In the Serbian and Thai context, except for large class size and learners' passiveness, learners' mixed ability was also reported as a problem for EFL teachers for teaching oral skills at the tertiary level (Bruner, Sinwongsuwat, & Radić-Bojanić, 2015). Along with these problems as mentioned above, Turkish EFL teachers faced other problems like learners' attitudes, teachers' lack of pedagogical knowledge, lack of technological support, and problems regarding curriculum and assessment procedures (Demir, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In most classrooms, especially at the basic education level, teachers are often challenged by the diversity of the students in the class-abilities, preferences, learning styles, and motivation, to name a few (Apairach & Vibulphol, 2015;Bruner et al, 2015;Kuehn, 2020;Phairee et al, 2008;Vibulphol, 2016). The 'standardized' teacher-centered instructional approach may not support the students in such classrooms effectively (Loima & Vibulphol, 2014Suthipiyapathra et al, 2019;Vibulphol, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many universities provide courses aimed to help learners to communicate fluently in diverse contexts. However, in-class oral activities as employed in a Chinese EFL classroom like scripted role-play and prepared oral presentations are apparently counterproductive in the context of genuine, authentic use of the target language (Bruner, Sinwongsuwat, & Radić-Bojanić, 2015).…”
Section: L2 Input-poor Environment and Learning For Communicative Purmentioning
confidence: 99%